Development and Validation of a Questionnaire to Measure Attitude change in Health Professionals after Completion of an Aboriginal Health and Cultural Safety Training Programme - Ryder, Courtney; Mackean, Tamara; Ullah, Shahid; Burton, Heather; Halls, Heather; McDermott, Dennis; Edmondson, Wendy (The Australian Journal of Indigenous Education, 2019)
Socially accountable health curricula, designed to decrease Aboriginal health inequities through the transformation of health professional students into culturally safe practitioners, has become a focal point for health professional programmes. Despite this inclusion in health curricula there remains the question of how to best assess students in this area in relation to the concept, of cultural safety and transformative unlearning, to facilitate attitudinal change. To address this question, this study developed a research questionnaire to measure thematic areas of transformative unlearning, cultural safety and critical thinking in Aboriginal Health for application on undergraduate and postgraduate students and faculty staff. The Likert-scale questionnaire was developed and validated through face and content validity. Test–retest methodology was utilised to determine stability and reliability of the questionnaire with 40 participants. The extent of agreement and reliability were determined through weighted kappa and intraclass correlation coefficient. Exploratory factor analysis was calculated to determine construct validity for questionnaire items. For the overall population subset the tool met good standards of reliability and validity, with 11 of the 15 items reaching moderate agreement (κ > 0.6) and an intraclass correlation coefficient of 0.72, suggesting substantial agreement. Cronbach's alpha was calculated above 0.7 for the thematic areas. The majority of items provided high factor loadings, low loading items will be reviewed to strengthen the tool, where validations of the revised tool with a larger cohort will allow future use to compare and determine effective teaching methodologies in Aboriginal health and cultural safety curricula.